2019
DOI: 10.1590/s0004-2803.201900000-80
|View full text |Cite
|
Sign up to set email alerts
|

Study of Lipid Biomarkers of Patients With Polyps and Colorectal Câncer

Abstract: BACKGROUND: Colorectal cancer (CRC) is one of the leading causes of cancer worldwide. Early diagnostic methods using serum biomarkers are required. The study of omics, most recently lipidomics, has the purpose of analyzing lipids for a better understanding of human lipidoma. The evolution of mass spectrometry methods, such as MALDI-MS technology, has enabled the detection and identification of a wide variety of lipids with great potential to open new avenues for predictive and preventive medicine. OBJECTIVE:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Other methods of analysis included direct infusion mass spectrometry (1 study) [32], Capillary electrophoresis-time of flight mass spectrometry (CE-TOFMS) (3 studies) [37,40,55], and Matrix Assisted Laser Desorption Ionization-Time of Flight mass spectrometry (MALDI-TOF MS) (1 study) [58] (Figure 2b). Thirty studies [23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][42][43][44][45][46][48][49][50]53,54,[56][57][58] employed untargeted metabolomic profiling, while 9 studies employed targeted metabolomics, either with a metabolite subset in mind to begin the study or as part of a validation of their untargeted data [22,25,26,28,35,47,51,52,55]. Of studies where the selections of analytical columns could be identified, 16 used a column that could identify polar and nonpolar compounds …”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
See 4 more Smart Citations
“…Other methods of analysis included direct infusion mass spectrometry (1 study) [32], Capillary electrophoresis-time of flight mass spectrometry (CE-TOFMS) (3 studies) [37,40,55], and Matrix Assisted Laser Desorption Ionization-Time of Flight mass spectrometry (MALDI-TOF MS) (1 study) [58] (Figure 2b). Thirty studies [23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][42][43][44][45][46][48][49][50]53,54,[56][57][58] employed untargeted metabolomic profiling, while 9 studies employed targeted metabolomics, either with a metabolite subset in mind to begin the study or as part of a validation of their untargeted data [22,25,26,28,35,47,51,52,55]. Of studies where the selections of analytical columns could be identified, 16 used a column that could identify polar and nonpolar compounds …”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
“…Thirty studies [23][24][25][27][28][29][30][31][32][34][35][36][37][38][39][40][42][43][44][45][46][48][49][50]53,54,[56][57][58] employed untargeted metabolomic profiling, while 9 studies employed targeted metabolomics, either with a metabolite subset in mind to begin the study or as part of a validation of their untargeted data [22,25,26,28,35,47,51,52,55]. Of studies where the selections of analytical columns could be identified, 16 used a column that could identify polar and nonpolar compounds [22,[25][26][27][28]31,33,36,38,…”
Section: Analytical Methods and Their General Performancementioning
confidence: 99%
See 3 more Smart Citations